« C’est une pièce qui rentre dans une autre pièce » : Normer les corps par l’éducation à la santé sexuelle en Suisse romande - Marlyse Debergh; Sophie Torrent (Genre, Sexualité et Société)
Drawing upon two ethnographic studies conducted in Western Switzerland – in a sexual education service for disabled people, and in a sexual health centre for the general public – this article demonstrates how gender is constructed through sexual health education. Deploying the theoretical paradigms of the Doing Gender Theory (West, Zimmerman, 2009), and the epistemology of ignorance (Tuana, 2006; 2004), this article presents one main finding: sexual health education programs (re)produce gender dynamics along a continuum, in different sexual health education programs designed for different audiences (youth, teenagers, adults). The analysis follows three lines: discourses, as well as medical and anatomical models, about fecundation and the clitoris; discourses about the social construction of puberty; definition and perception of sexual intercourse.